Dolomite Relief in the Žibrše Hills - Blaž Komac (Acta Geographica Slovenica, 2004)
The paper describes the dolomite relief of the Žibrše hills where dells are a characteristic relief feature. It discusses the main geomorphological characteristics and genesis of the relief. Carbonate rock covers almost one half of Slovenia's surface area, of which dolomite comprises about one quarter. Dolomite relief with dells, which cover a little less than one tenth of the dolomite areas, is par-ticularly interesting. The relief with dells is neither typical fluviodenudational relief because there are no surface water streams nor typical karst relief because dells are linear relief features. Their occurrence and development have not previously been studied in detail. The paper describes the principal characteristics of dolomite relief with dells in the Žibrše hills northeast of Logatec. Considered geomorphologically, the studies of the geological structure and chemistry stud-ies indicate that the dells were formed by periglacial processes during the cold periods of the Pleistocene, and due to the carbonate nature of the rock, by karst processes as well.